Comparative analysis of survival between elderly and non-elderly severe sepsis and septic shock resuscitated patients - Palomba,Henrique (2015)
Objective To compare outcomes between elderly (≥65 years old) and non-elderly (<65 years old) resuscitated severe sepsis and septic shock patients and determine predictors of death among elderly patients.Methods Retrospective cohort study including 848 severe sepsis and septic shock patients admitted to the intensive care unit between January 2006 and March 2012.Results Elderly patients accounted for 62.6% (531/848) and non-elderly patients for 37.4% (317/848). Elderly patients had a higher APACHE II score [22 (18-28)versus 19 (15-24); p<0.001], compared to non-elderly patients, although the number of organ dysfunctions did not differ between the groups. No significant differences were found in 28-day and in-hospital mortality rates between elderly and non-elderly patients. The length of hospital stay was higher in elderly compared to non-elderly patients admitted with severe sepsis and septic shock [18 (10-41)versus 14 (8-29) days, respectively; p=0.0001]. Predictors of death among elderly patients included age, site of diagnosis, APACHE II score, need for mechanical ventilation and vasopressors.Conclusion In this study population early resuscitation of elderly patients was not associated with increased in-hospital mortality. Prospective studies addressing the long-term impact on functional status and quality of life are necessary.